A3 Adenosine receptors mediate oligodendrocyte death and ischemic damage to optic nerve. Issue 2 (6th December 2013) - González‐Fernández, Estíbaliz; Sánchez‐Gómez, María Victoria; Pérez‐Samartín, Alberto; Arellano, Rogelio O.; Matute, Carlos
<x xml:space="preserve">Abstract</x> Adenosine receptor activation is involved in myelination and in apoptotic pathways linked to neurodegenerative diseases. In this study, we investigated the effects of adenosine receptor activation in the viability of oligodendrocytes of the rat optic nerve. Selective activation of A3 receptors in pure cultures of oligodendrocytes caused concentration‐dependent apoptotic and necrotic death which was preceded by oxidative stress and mitochondrial membrane depolarization. Oligodendrocyte apoptosis induced by A3 receptor activation was caspase‐dependent and caspase‐independent. In addition to dissociated cultures, incubation of optic nerves ex vivo with adenosine and the A3 receptor agonist 2‐CI‐IB‐MECA(1‐[2‐Chloro‐6‐[[(3‐iodophenyl)methyl]amino]‐9H‐purin‐9‐yl]‐1‐deoxy‐N‐methyl‐b‐D‐ribofuranuronamide)‐induced caspase‐3 activation, oligodendrocyte damage, and myelin loss, effects which were prevented by the presence of caffeine and the A3 receptor antagonist MRS 1220 (N‐[9‐Chloro‐2‐(2‐furanyl)[1, 2, 4]‐triazolo [1, 5‐c]quinazolin‐5‐yl]benzene acetamide). Finally, ischemia‐induced injury and functional loss to the optic nerve was attenuated by blocking A3 receptors. Together, these results indicate that adenosine may trigger oligodendrocyte death via activation of A3 receptors and suggest that this mechanism contributes to optic nerve and white matter ischemic damage. GLIA 2014;62:199–216